Sosiologi Lembaga Pendidikan: Konstruksi Ketahanan Sosial Siswa Madrasah Tsanawiyah dalam Menghadapi Tekanan Akademik dan Budaya Digital di MTs Negeri 1 Banyumas - Atikoh Khasanah; Muh. Hanif (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This article examines the construction of social resilience among students of Madrasah Tsanawiyah (MTs) Negeri 1 Banyumas in facing academic pressure and digital culture through the lens of the sociology of educational institutions. Initial classroom observations in the accelerated program indicate that academic pressure is heightened due to additional instructional hours, while digital culture emerges as a source of distraction that reduces concentration and affects students’ emotional well-being. Survey data reveal that rules on gadget use, peer support, and religious values play a crucial role in shaping students’ social resilience. Previous studies tend to be normative and administrative, emphasizing school discipline or gadget regulations without unpacking the social mechanisms within the madrasah. This article addresses that gap with three focal points: (1) analyzing gadget-use rules as a strategy to limit the negative impact of digital culture, (2) explaining the role of peer groups as spaces for sharing academic pressure and social concerns, and (3) assessing religious values as a moral framework for students in engaging with digital content. Using a qualitative approach, this study aims to demonstrate how social relations, institutional norms, educational authority, and the experiences of students, teachers, and parents shape everyday educational practices. The contribution of this article goes beyond case description, seeking to build theoretical arguments about how educational institutions function as social arenas that produce trust, identity, discipline, solidarity, and social change. The findings are expected to enrich discussions on the sociology of Islamic education in Indonesia and offer recommendations for strengthening institutional governance based on field data.